Effect of Time-Delay in the Logistic Growth Model Driven by Weak Signal and White Noise - 周玉荣 (Chinese physics letters, 2010)
Effect of delayed time in the logistic growth model subject to weak periodic signal and correlated multiplicative and additive white noise is investigated. Using small time delay approximation, we obtain the expression of the signal-to-noise ratio （SNR）. It is found that the SNR is non-monotonic functions of the delayed times, the system parameters, the intensities of the multiplicative and additive noise, as well as the correlation strength of the two noises.